In vitro effect of fatty acids identified in the plasma of obese adolescents on the function of pancreatic β-Cells (2017)
ABSTRACT: The increase in circulating free fatty acid (FFA) levels is a major factor that induces malfunction in pancreatic β-cells. We evaluated the effect of FFAs reconstituted according to the profile of circulating fatty acids found in obese adolescents on the viability and function of the murine insulinoma cell line (mouse insulinoma [MIN6]). Methods: From fatty acids obtained commercially, plasma-FFA profiles of three different youth populations were reconstituted: obese with metabolic syndrome; obese without metabolic syndrome; and normal weight without metabolic syndrome. MIN6 cells were treated for 24 or 48 hours with the three FFA profiles, and glucose-stimulated insulin secretion, cell viability, mitochon-drial function and antioxidant activity were evaluated. Results: The high FFA content and high polyunsaturated ω6/ω3 ratio, present in plasma of obese adolescents with metabolic syn- drome had a toxic effect on MIN6 cell viability and function, increasing oxidative stress and decreasing glucose-dependent insulin secretion. Conclusion: These results could help to guide nutritional management of obese young individuals, encouraging the increase of ω-3-rich food consumption in order to reduce the likelihood of deterioration of β-cells and the possible development of type 2 diabetes mellitus.